PENINGKATAN KOMPETENSI SOSIAL SISWA TENTANG KONSEP PERGAULAN YANG EFEKTIF DENGAN MODEL ROLE PLAYING DALAM LAYANAN KLASIKAL - Martinus Ghea (Universitas Sultan Ageng Tirtayasa, 2019)
Abstract This research is a classroom action research in counseling (PTK-BK) conducted by the researchers themselves. Retrieval of data in this study was carried out using observation techniques to determine the implementation of classical services conducted by counselors and immediate assessment tests (laiseg) to determine the level of understanding of students in effective social concepts through action analysis in cycle 1 and cycle 2. The results showed through role playing models proven to be able to improve the results of classical services on the topic of Effective Relationship in class XII-MIPA 1 of SMAN 2 Kota Tangerang Selatan Banten Province, evident from the average score of the level of understanding obtained in classical services in Cycle I = 15.25 (61%), Cycle II = 25 (110%). Thus, through the Role Playing model, it is proven that it can create a classic service atmosphere that pleases and attracts the interest of students, because the counselor is able to use this model well, as evidenced by the observations on the implementation of classical services, which were initially inactive. in classical service activities, being in cycle II Students look enthusiastic and are interested in how counselors / counselors are delivered. Keywords: Classic services, Contextual Teaching and learning (CTL) models.